The Electronic Road Pricing System Planning: A Scenario of Curbing Congestion Issues on an Arterial Road in Makassar City, Indonesia - Erning Ertami Anton; Andi Batari Angka; Ronaldo Nugrah Bintaro; Lavista Anggreini Lagamu (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
This study aims to analyze the traffic performance on arterial roads in Makassar City in the present and future with the implementation of Electronic Road Pricing, as well as analyze how many tariffs can be applied when Electronic Road Pricing (ERP) is used. The data were collected from traffic surveys and questionnaires distributed to users of four-wheeled and two-wheeled vehicles. From the data, the existing traffic conditions on the road were analyzed, and the probability of moving road users was calculated during the implementation of ERP. Furthermore, the Willingness To Pay method determines the rates that can be applied. The results of the research show that when ERP is implemented on the Andi Pangeran Pettarani Road, there will be a 40% reduction in traffic flow due to the route changes and a 42% reduction in traffic flow due to the modal shifts. This affects improving traffic performance in the future, where the existing condition of this road segment which was initially at LoS D and E, can be increased to LoS B and C. The tariff that can be applied to the ERP system is Rp 8,838 for four-wheeled vehicles or more and Rp 4,343 for two-wheeled vehicles